2006
DOI: 10.4049/jimmunol.176.7.4419
|View full text |Cite
|
Sign up to set email alerts
|

CSMD1 Is a Novel Multiple Domain Complement-Regulatory Protein Highly Expressed in the Central Nervous System and Epithelial Tissues

Abstract: In this study, we describe the identification and in vitro functional activity of a novel multiple domain complement regulatory protein discovered based on its homology to short consensus repeat (SCR)-containing proteins of the regulators of complement activation (RCA) gene family. The rat cDNA encodes a predicted 388-kDa protein consisting of 14 N-terminal CUB domains that are separated from each other by a SCR followed by 15 tandem SCR domains, a transmembrane domain, and a short cytoplasmic tail. This prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
171
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 52 publications
3
171
0
Order By: Relevance
“…Loss of CSMD1 expression increased cell proliferation. This agrees with studies that showed expression of the rat ortholog of CSMD1 is low in brain regions exhibiting high levels of cell proliferation (4). Similarly, a recent study has demonstrated that increasing miRNA-10b expression in HepG2 hepatocellular carcinoma cells resulted in decreased CSMD1 expression and increased proliferation (17).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Loss of CSMD1 expression increased cell proliferation. This agrees with studies that showed expression of the rat ortholog of CSMD1 is low in brain regions exhibiting high levels of cell proliferation (4). Similarly, a recent study has demonstrated that increasing miRNA-10b expression in HepG2 hepatocellular carcinoma cells resulted in decreased CSMD1 expression and increased proliferation (17).…”
Section: Discussionsupporting
confidence: 79%
“…Formation of such structures is an indicator of extensive actin polymerisation (23). Previous studies have revealed that the rat ortholog of CSMD1 colocalizes with F-actin (4,24). Thus CSMD1 may have an inhibitory effect on actin assembly or the signalling processes that impact upon the regulation of this process (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other regulatory proteins, such as factor H, factor I, and C4 binding protein, also down-regulate complement activation . CUB and Sushi multiple domains 1 (CSMD1), CSMD2, and CSMD3 have been proposed to have a role in regulating complement activation and inflammation in the developing CNS (Nagase et al, 2001;Kraus et al, 2006). C4b, C3b, iC3b, C3dg, and C3d bind to CR1 and complement receptor type 2 (CR2) on B lymphocytes and enhance antibody response and long-term memory of B-cells.…”
Section: Introductionmentioning
confidence: 99%
“…CSMD2 is a recently cloned gene (39) whose functionality still needs to be identified. Recently, CSMD1, a gene with high structural similarity to CSMD2, has been implicated in the inhibition of complement activation (40), which could suggest a com-mon functionality. In addition, the results from our analysis along with previous genome-wide association studies also identified several SNPs from the newly associated TNFAIP3 locus (rs643571 at P ϭ 6 ϫ 10 Ϫ3 and rs6915853 at P ϭ 2 ϫ 10 Ϫ3 in our study).…”
Section: ϫ3mentioning
confidence: 99%